Samuel Ibn Tibbon on the Book of Job - Eisen, Robert (AJS review, 1999)
Samuel ibn Tibbon (died ca. 1232) is best known as the translator of Maimonides' Guide of the Perplexed. But as Aviezer Ravitzky has shown in his doctoral dissertation and in a series of recent articles, ibn Tibbon was an important thinker in his own right. First and foremost, ibn Tibbon appears to have been the earliest significant interpreter of Maimonides' philosophical thought. He was also one of the most influential. While there had been suspicions, even during his lifetime, that Maimonides held radical esoteric philosophical views, ibn Tibbon was the first to lend sophistication to this viewpoint by developing an elaborate system of interpretation for unlocking the secrets of the Guide, one that would have a significant impact on subsequent interpreters of Maimonides.